The Affecting of Demographic Factors on Utilization of Postpartum Health Service - Kusmirawati, Kusmirawati; Alfiasari, Fadila; Maulinda, Amanda Via; Gaurinindi, Melinda Febianca; Noer, Afifah; Fadhila, Shofia Nur; Annisaa, Salwa; Hapsari, Putri; Ramadhan, Septyandi; Adiansa, Rendi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Based on research states that the prevalence rate of complete postpartum visits (KF) in Indonesia is 37%, where this figure has increased from 2013 of 32.1%. The problem with the achievement of postpartum visits in Indonesia is that the underdeveloped areas mentioned in Presidential Decree Number 63 of 2020, namely North Sumatra, Central Sulawesi, Maluku, Papua and West Papua, occupy the bottom 6 provinces in the complete postnatal visit. The province of West Papua is the region with the lowest KF coverage rate in Indonesia. Subjects and Method: Metaanalysis conducted using the PRISMA systematic guidelines. Population= puerperium mother, Intervention= Urban, Comparison= Rural, Outcome= Utility of postnatal health service. The process of searching for articles was carried out between 2005 and 2021 using a database search engine consisting of; PubMed, Science Direct, Springer Link, and Google Scholar. Based on the database search, there were ten articles that met the criteria with a crosssectional design and observational studies and research that discussed demographic factors (urban & rural) on health care facilities. Results: The results of the analysis had high heterogeneity between studies I2= 94%, so that the Random Effect Model was used. Postnatal mothers living in urban areas increased by 1.48 times in utilizing postnatal care health services compared to postnatal mothers living in rural areas. however it was not statistically significant (SMD= 1.48; 95% CI= 0.90 to 2.44; p= 0.012). Conclusion: Postpartum women who live in urban areas use postpartum health services more than postpartum women who live in rural areas. Keywords: postpartum, postnatal visit, demographic factorsCorrespondence: Kusmirawati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: rendiadiansa@student.uns.ac.id Mobile Number: 08816008735.Journal of Health Policy and Management (2022), 07(03): 176-184https://doi.org/10.26911/thejhpm.2022.07.03.01